GREEN HUMAN RESOURCE MANAGEMENT AND JOB PURSUIT INTENTION: MEDIATING ROLE OF CORPORATE SOCIAL RESPONSIBILITY AND ORGANIZATIONAL REPUTATION - Priskilla E.E. Napitupulu; Janice Carysa Siahaya; Tania Monica Potu (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
This study investigates the influence of Green Human Resource Management (GHRM) on Corporate Social Responsibility (CSR), Organizational Readiness (OR), and Job Performance Improvement (JPI) within a sustainable organizational framework. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4, data were collected from employees across various sectors to examine the direct and indirect relationships among the constructs. The findings reveal that GHRM significantly and positively affects both CSR and OR. While GHRM does not directly influence JPI, it enhances JPI through the mediating role of OR. Furthermore, the relationship between CSR and JPI was found to be statistically insignificant. These results suggest that fostering an environmentally responsible HRM approach not only supports broader corporate social goals but also enhances the organization’s readiness for change, which in turn leads to better job performance. The research contributes to the growing body of literature on sustainable HRM practices and offers practical implications for managers aiming to build resilient and high-performing organizations. Limitations include the study's cross-sectional design and the focus on a specific context, which may affect generalizability. Future research is encouraged to use longitudinal approaches and consider additional mediating factors to deepen the understanding of these dynamics in different industries and cultural settings.